The Duty of the Federal Republic of Germanyto Participate in the European Integration - Haack, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In its preamble, the Basic Law of the Federal Republic of Germany admits Germany`s participation in the process of European unification. This aim is specified by Article 23 of the Basic Law: as a result, the Federal Republic of Germany is required by its constitution to participate in the EU. This provision amounts to a state objective (Staatszielbestimmung). At the same time, Article 23 of the Basic Law imposes limits on this duty.
Keywords: Federalny Sąd Konstytucyjny; Ustawa Zasadnicza Federalnej Republiki Niemiec; prawo unijne; the Basic Law of the Federal Republic of Germany; the Federal Constitutional Court; EU law